Feasibility of Replacement of Cement with Copper Slag in Flyash Based Bricks - S, Harish; S, Karthik; Raja Mohan K, Saravana (International Journal of Engineering and Technology, 2018)
Cement manufacturing industry has been a great contributor to global warming which poses global threat. This novel paper investigates the possibilities of reducing the amount of cement used in a conventional flyash brick by replacing the cement with copper slag in various proportions to make way for substantial construction. Flyash bricks contribute less to global warming compared to chamber bricks, which involves lot of burning. Further substitution of cement with copper slag would significantly reduce its damage potential as copper slag itself is a by-product from copper manufacturing. A conventional flyash brick contains 5% of the entire mix as cement. This paper aims to replace the cement in flyash bricks in successive percentages of the entire mix i.e 1%, 2%, 3%, 4% and 5% with copper slag. The brick samples are then subjected to mechanical tests and durability tests as per IS 3495:1992 and IS 13757:1993. These data of the samples are compared with the normal flyash bricks to find the best proportion. The greatest advantage is the economic factor involved as 1kg of copper slag costs only 16% of that of cement, providing a greater scope for the implementation of this research in reality.